PENINGKATAN PEMBANGUNAN SOSIAL MELALUI OPTIMALISASI PROGRAM KAMPUNG TEMATIK KAMPUNG PURUN , KALIMANTAN SELATAN - Sihotang, Dwi Rahyanti; Nugroho, Fentiny (Jurnal Pembangunan Manusia, 2021)
Social development should be able to evenly touch all areas, where welfare is felt by all groups of society. One of the areas in Indonesia that still has many social problems such as unemployment, poverty, health, or regional planning is kampong. Various programs have been carried out by the government as an effort to improve social development so that the kampongs are no longer in a condition called distorted development. One of the kampong improvement efforts in Indonesia is the thematic village program. Several regions in Indonesia use thematic kampongs as a means of promoting local potential, regional development solutions, or creating new ideas to achieve community welfare. The implementation of thematic villages has been successful in several areas such as Semarang City, Malang City, Bandung Regency, Bogor City, and Banjarbaru City. This study attempts to analyze one thematic kampong that is able to survive and get attention to foreign countries, namely Kampung Purun in Banjarbaru City, South Kalimantan. This study aims to analyze the Kampung Purun program in increasing social development through social development strategies, as well as social capital and supporting and obstacle factors. This research is expected to produce novelty considering previous studies on thematic kampong have not focused too much on social development strategies and community’s capital. This study uses a qualitative approach with descriptive methods. Data collection techniques using literature and documentary studies, in-depth interviews, and observation. The results showed that the social development strategies in the thematic kampong of Kampung Purun were government, community, and individual strategies. The capital of the community consisted of physical, financial, environmental, technological, human, social, and political capital. To enhance the development of Kampung Purun, this study employed a SWOT analysis (Strength, Weakness, Opportunity, Threat).